Quizizz Solusi Belajar dari Rumah (BDR) Mandiri di Masa Pandemi COVID-19 (LP3 Universitas Negeri Semarang, 2022)
Tujuan Best Practice ini adalah mendeskripsikan cara dan hasil pelaksanaan pembelajaran sebagai guru mata pelajaran Bahasa Indonesia melalui strategi penggunaan aplikasi Quizizz Solusi BDR Mandiri di Masa Pandemi Covid-19. Dalam Best Practice ini strategi yang dilakukan penulis adalah 1) membuat soal Bahasa Indonesia melalui word; 2) membuat soal Bahasa Indonesia dengan menggunakan aplikasi Quizizz; 3) melatihkan soal dari aplikasi Quizizz, dan 4) melihat hasil nilai yang diperoleh melalui Penilaian Harian (PH) menggunakan CBT E-Learning madrasah. Berdasarkan nilai yang dihasilkan saat Semester 1 pada Penilaian Harian Tema 1 sampai dengan Tema 5, diperoleh Nilai Minimum 80, Nilai Rata-rata 89, dan Nilai Maksimum 100 dengan Nilai Ketuntasan 100%. Penilaian Harian Tema 6 sampai dengan Tema 9 saat Semester 2, diperoleh Nilai Minimum 80, Nilai Rata-rata 92, dan Nilai Maksimum 100 dengan Nilai Ketuntasan 100%. Penerapan aplikasi Quizizz sebagai instrumen pembelajaran Bahasa Indonesia yang dilandasi pembelajaran inkuiri terbimbing berbantuan aplikasi game selama pandemi Covid-19, dapat membangkitkan kesadaran belajar dalam proses belajar di rumah (BDR) selama pandemi Covid-19.The aim of writing this Best Practice is to describe the way and the result of instructional process conducted by Bahasa Indonesia teacher through the application of Quizizz, solution for Independent Learning from home during the pandemic of Covid 19. In this Best Practice the strategy applied by the writer are (1) writing Bahasa Indonesia problems using MS Office Words; 2) writing Bahasa Indonesia problems using Quizizz application; 3) training students with problems in Quizizz application; 4) collecting scores acquired through the Daily Assessment using CBT in Madrasah (school) E-Learning application. Based on scores acquired in 1st semester on Daily Assessment of 1st Theme up to Theme 5, a minimum scores of 80, average scores of 89, and a maximum score of 100 with Minimum Mastery Criteria of 100% had been acquired by the students. For Daily Assessment 6th uo to 9th at the second semester, the students have acquired a minimum scores of 80, average scores of 92, and a maximum score of 100 with Minimum Mastery Criteria of 100%. It can be deduced then, that appliying Quizizz as an instructional instrument of Bahasa Indonesia, based on guided inqury leaning with the assistance of game application during the pandemic of Covid 19, has successfully evoked students’ learning awareness in the independent learning process of Bahasa Indonesia during the pandemic of Covid-19.